2005
DOI: 10.1152/ajpheart.00749.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extreme hemodilution with hemoglobin-based O2 carriers on microvascular pressure

Abstract: -A surface-modified polyethylene glycol-conjugated human hemoglobin (MP4) and ␣␣-cross-linked human hemoglobin (␣␣Hb) were used to restore oxygen carrying capacity in conditions of extreme hemodilution (hematocrit 11%) in the hamster window model preparation. Changes in microvascular function were analyzed in terms of effects on capillary pressure and functional capillary density (FCD). MP4, at 1.0 Ϯ 0.2 g/dl blood concentration, significantly lowered mean arterial pressure (MAP) below baseline (99.6 Ϯ 7.6 mmH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
(50 reference statements)
5
21
0
Order By: Relevance
“…As in previous studies, hemodilution in combination with a vasoconstrictor effect caused a significant decrease in FCD (13). The lowest FCD coincided with the most pronounced vasoconstriction (Figures 2).…”
Section: Systemic Versus Microvascular Responsesupporting
confidence: 85%
See 2 more Smart Citations
“…As in previous studies, hemodilution in combination with a vasoconstrictor effect caused a significant decrease in FCD (13). The lowest FCD coincided with the most pronounced vasoconstriction (Figures 2).…”
Section: Systemic Versus Microvascular Responsesupporting
confidence: 85%
“…45%, and arterial O 2 partial pressure (Pa O 2 ) greater than 50 mm Hg; and (2) microscopic examination of the tissue in the chamber observed under a 3650 magnification did not reveal signs of low perfusion, inflammation, edema, or bleeding. Hamsters are a fossorial species with a lower arterial PO 2 ; however, their microvascular PO 2 distribution in the chamber window model is similar to that of other rodents (13).…”
Section: Inclusion Criteriamentioning
confidence: 86%
See 1 more Smart Citation
“…Our previous studies with this experimental model and CFHs introduced in an extreme exchange transfusion protocol found that the pressure drop in the microvascular network was located in different segments of the system. 39 A greater pressure drop and corresponding vasoconstriction prior to the microcirculation was found for PBH and ␣␣Hb, while for MP4 more of the systemic pressure was transmitted to the microcirculation. Maintenance of microvascular perfusion pressure by MP4 should be related to the lack of vasoconstriction observed in the present study.…”
Section: Cardiac Index and Vascular Resistancementioning
confidence: 92%
“…The most affected segment appears to be the microcirculation with a reduction of the functional capillary density [60]. It has been observed that haemoglobin solutions with different O 2 affinity caused different degrees of vasoconstrictions [61,62].…”
Section: Modified Haemoglobin Solutionsmentioning
confidence: 99%